Pengaruh Good Corporate Governance, Ukuran Perusahaan Dan Leverage Terhadap Kinerja Keuangan : Studi kasus Perusahaan Manufaktur sektor Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2020-2022 - Kholifah, Rofiu Nur; Kristiyanti, LMS; Ningsih, Suhesti (Nur Science Institute, 2025)
This study aims to examine the effect of good corporate governance (GCG), firm size, and leverage on financial performance in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. A quantitative approach was applied with purposive sampling, resulting in 29 companies and 87 firm-year observations. Secondary data were collected from annual reports published on the IDX website. Data were analyzed using multiple linear regression with SPSS 25. The findings reveal that GCG, measured by the board of directors, board of commissioners, and audit committee, does not significantly affect financial performance. In contrast, firm size, proxied by the natural logarithm of total assets, and leverage, proxied by the debt-to-equity ratio (DER), have a positive and significant impact on financial performance measured by return on assets (ROA). These results suggest that larger firm size and effective leverage management contribute to better financial performance, while GCG practices during the study period have not shown substantial influence.